2019
DOI: 10.1371/journal.pone.0213754
|View full text |Cite
|
Sign up to set email alerts
|

Use of infrared thermography in the detection of superficial phlebitis in adult intensive care unit patients: A prospective single-center observational study

Abstract: Common methods to detect phlebitis may not be sufficient for patients in the intensive care unit (ICU). The goal of this study was to investigate the feasibility of infrared (IR) thermography to objectively detect phlebitis in adult ICU patients. We included a total of 128 adult ICU-patients in a pilot and subsequent validation study. Median [interquartile range] age was 62 [54–71] years and 88 (69%) patients were male. Severity of phlebitis was scored using the visual infusion phlebitis (VIP)-score, ranging f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 24 publications
(30 reference statements)
0
6
0
1
Order By: Relevance
“…Furthermore, recent studies demonstrated the validity and applicability of using the cell phones-connected thermal cameras for different clinical implications. [20][21][22][23] FLIR ONE is a LWIR smartphone-connected thermal camera. It is a light hand-held device, easy to use, noninvasive, cheap, reliable, and an objective tool that provides an immediate reading for skin temperature and reflects the perfusion status of the limb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent studies demonstrated the validity and applicability of using the cell phones-connected thermal cameras for different clinical implications. [20][21][22][23] FLIR ONE is a LWIR smartphone-connected thermal camera. It is a light hand-held device, easy to use, noninvasive, cheap, reliable, and an objective tool that provides an immediate reading for skin temperature and reflects the perfusion status of the limb.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies demonstrated the validity and applicability of using the cell phones-connected thermal cameras for different clinical implications. 20–23 …”
Section: Discussionmentioning
confidence: 99%
“…The complications of infusion include phlebitis, hematoma, infiltration, thrombophlebitis, air embolism (Chang, Chen, Wang, & Wang, n.d.). Phlebitis itself is an inflammatory reaction that occurs in veins that are painful, reddish, swollen, hot, induration (hardening) in the puncture area, and hardening along the veins (Doesburg et al, 2019). Phlebitis is characterized by redness of the puncture area, pain, swelling, hardening or induration, hardening of the veins, and heat (Lee et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aan de hand van een voorbeeld, waarbij het doel is flebitis in een vroeg stadium te kunnen onderkennen, wordt in dit artikel het belang van deze methode toegelicht. 1 de kwaliteit van de zorg verder te vergroten. Dat heeft voordelen voor de patiënt, maar zou ook tot taakverlichting kunnen leiden bij verpleegkundigen.…”
Section: Verpleegkundige Relevantieunclassified